The Image of the Black Sea in Crimean Marketing Chrematonyms. Introduction to Research - Tomasik, Samuela (Poznańskie Studia Slawistyczne, 2024)
This article is devoted to the names of commercial and service points on the Crimean Peninsula. Onomastic research focuses on answering the question of how the creators of names reflect the Black Sea and the entire coastal space. The author also seeks answers to the question regarding general naming tendencies that can be noticed in the analyzed units. The analyzed material showed that two types of names dominate in Crimea. These are traditional and modern names. The Black Sea depicted in them appears to be benevolent, but also dangerous. The trade names therefore show that the inhabitants of the Crimean Peninsula appreciate their past and tradition, but are also aware of and need for changes regarding services, goods and their naming.